The diet of a specialist nectarivore in Australia: The little red flying‐fox (Pteropus scapulatus, Pteropodidae). (22nd January 2022) - Bradford, Matt; Venz, Melanie; Bell, Karen L.; Hogan, Luke; Smith, Geoffrey C.; Eby, Peggy; Eyre, Teresa J.; McKeown, Adam; Vanderduys, Eric; MacDonald, Stewart; Westcott, David
Abstract: The little red flying‐fox ( Pteropus scapulatus, Pteropodidae) is the most widely distributed of the four Australian mainland flying‐fox ( Pteropus ) species. They move very large distances following foraging resources and congregate in large numbers which often causes human‐animal conflict. To better understand the resources that drive these movements and aggregations, we investigated the diet of the little red flying‐fox using data from five sources: (i) faecal eDNA metabarcoding of field sampled little red flying‐foxes; (ii) identification of foraging locations through satellite tracking; (iii) a literature search; (iv) a search of online databases; and (v) an expert survey. Our sources revealed a specialist nectarivore diet containing 204 species, dominated by floral products from the plant family Myrtaceae. We consider a small number of widely occurring and structurally dominant Myrtaceae, particularly from the genera Corymbia, Eucalyptus and Melaleuca, as major diet species that regularly drive mass aggregations. In addition, we consider a moderate number of species dominated by the Myrtaceae as important diet species and a large number of species from diverse taxa as supplementary diet species. Fruit represents approximately 5% of the diet suggesting that the little red flying‐fox is unlikely to be a major pest of horticultural crops or disperser of weeds. The combination of long‐distance movement and a wide range of diet species results in a long‐distance pollination service to many plant species which likely promotes genetic mixing between isolated populations of plants. Our understanding of the little red flying‐fox diet allows us to better predict mass migrations and aggregations at a continental scale and allows us to clearly identify key foraging habitat so that informed management decisions can be made. Abstract : The little red flying‐fox moves large distances following foraging resources and congregate in large numbers which often causes human‐animal conflict. We revealed a specialist nectarivore diet containing 204 species, dominated by floral products from the plant family Myrtaceae. Our understanding of the little red flying‐fox di et al lows us to better predict mass migrations and aggregations at a continental scale and allows us to clearly identify key foraging habitat so that informed management decisions can be made.